DIVERSITY AND DENSITY OF TERMITE MOUNDS IN BHADRACHALAM FOREST REGION, ANDHRA PRADESH - A. NAGESWARA RAO,; C. H. SRAVANTHY,; C. H. SAMMAIAH, (The Bioscan, 2012)
To determine and quantify the diversity and density of mound-building termites, we were observed Bhadrachalam forest region located at Khammam district, Andhra Pradesh, India. In the present study we observed that the termite fauna was enriched with 7 species, belonging to 2 genera of family Termitidae. We investigated chemical and physical properties of termite mound at forest region. Their effects on the development of native plant species. Carbon, Phosphorus, Potassium levels in the termite mounds were significantly elevated by 1.16 pap, 12.63 kg/acre and 15.63 kg/acre respectively. While termites mound significant differences more in Manganese, Iron, Copper, Zinc, Sulphur and pH concentration was observed. Average density of termite mounds of different study areas was studied.